Corazon Aquino - Chua-Eoan, Howard (New York : Chelsea House, 1988)
A biography of the woman who rose to political prominence after the death of her husband and was elected president of the Philippines in 1986.
Cover title: Aquino.
Includes index.
Bibliography: p. 108.
Basic Ed. Students
Keywords: Aquino, Corazon Cojuangco -- Juvenile literature; Aquino, Corazon Cojuangco; Presidents -- Philippines -- Biography -- Juvenile literature; Heads of state; Presidents -- Philippines